Interferon-induced transmembrane protein-3 rs12252-C is associated with rapid progression of acute HIV-1 infection in Chinese MSM cohort. (15th May 2015) - Zhang, Yonghong; Makvandi-Nejad, Shokouh; Qin, Ling; Zhao, Yan; Zhang, Tong; Wang, Lili; Repapi, Emmanouela; Taylor, Stephen; McMichael, Andrew; Li, Ning; Dong, Tao; Wu, Hao
<x xml:space="preserve">Abstract</x> Background: The interferon-inducible transmembrane protein-3 (IFITM3) is a protein that restricts multiple pathogenic viruses such as influenza virus. The single-nucleotide polymorphism rs12252-C, which is rare in Caucasian populations, but much more common in the Han Chinese population, has been found in much higher homozygous frequency in patients with severe acute influenza. Until now, there has been no study on the effect of this genetic variant on the clinical control of other viral infections. Objectives: To investigate the impact of IFITM3-rs12252 genotypes on primary HIV-1 infection progression in an acute HIV-1-infected cohort in Beijing (PRIMO), China. Design and methods: We identified IFITM3-rs12252 genotypes of 178 acute HIV-1-infected patients and 196 HIV-negative candidates from the PRIMO cohort. HIV-1 viral load and CD4+ T-cell counts were monitored at multiple time points during the first year of infection, and the association between IFITM3-rs12252 genotype and disease progression was evaluated. Results: The current study shows that the IFITM3-rs12252 genetic variant affects the progression of HIV-1 infection, but not the acquisition. A significantly higher frequency of the CC/CT genotypes was found in rapid progressors compared to nonprogressors. Patients with CC/CT genotypes showed an elevated peak viremia level and significantly lower CD4+ T-cell count at multiple time points during the first year of primary infection, and a significantly higher risk of rapid decline of the CD4+ T-cell count to below 350 cells/μl. Conclusion: A novel association between IFITM3 gene polymorphism and rapid disease progression is reported in an acute HIV-1-infected MSM cohort in China.